2003
DOI: 10.1136/jcp.56.2.129
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of flow cytometry, bone marrow biopsy, and bone marrow aspirates in the detection of lymphoid infiltration in B cell disorders

Abstract: Aims: To evaluate the diagnostic value of bone marrow aspirates, trephine biopsies (BMB), and flow cytometry (FC) in the assessment of bone marrow infiltration in chronic lymphoid disorders. Methods: Investigations were carried out in 110 diagnostic and follow up specimens from B cell disorders, namely: chronic lymphocytic leukaemia (CLL; 65), non-Hodgkin's lymphoma (NHL; 39), and hairy cell leukaemia (HCL; 6). A selected panel of monoclonal antibodies was used both for FC and immunohistochemistry. Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 19 publications
4
47
1
4
Order By: Relevance
“…In our experience, less than 3% of cases of CLL had absent or limited and not diagnostic lymphoid infiltration (data not shown), in contrast with up to 10% negative BM biopsies reported in CLL by Sah et al 28 Moreover, the use of BM biopsies in our study allowed us to evaluate retrospectively a large series of CLL patients with adequate follow-up (median 58 months).…”
Section: Discussionmentioning
confidence: 56%
“…In our experience, less than 3% of cases of CLL had absent or limited and not diagnostic lymphoid infiltration (data not shown), in contrast with up to 10% negative BM biopsies reported in CLL by Sah et al 28 Moreover, the use of BM biopsies in our study allowed us to evaluate retrospectively a large series of CLL patients with adequate follow-up (median 58 months).…”
Section: Discussionmentioning
confidence: 56%
“…No entanto, em função da similaridade da morfologia muitas vezes observada nesse material, sua classificação e, consequentemente, a escolha do tratamento são bastante dificultados, exigindo a confirmação diagnóstica por meio da biópsia de outros órgãos, como baço e linfonodos (1,10,14) .…”
Section: Introductionunclassified
“…A biópsia de medula óssea (MO) ou mesmo de outros órgãos linfoides para o diagnóstico de síndromes linfoproliferativas crônicas, todavia, além de demoradas, invasivas, que necessitam de técnicas complementares de diagnóstico, como a imuno-histoquímica, exigem a presença de profissionais treinados e altamente qualificados para a diferenciação dessas neoplasias (4,14) . Diversos autores têm sugerido a utilização da imunofenotipagem por citometria de fluxo aliada à citologia convencional como método rápido e não invasivo de diagnós-tico alternativo para síndromes linfoproliferativas (2-7, 9, 11, 14, 15) .…”
Section: Introductionunclassified
“…For a number of cases with a limited number of lymphoma cells involving bone marrow, FCM may assist with diagnosis (18,19). However, there may be different results between BMA/BMB and FCM (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrow karyotype was 46, XY [20]. Flow cytometric (FCM) analysis revealed that CD45 + CD19 + cells, which were potentially abnormal B lymphocytes, expressed human leukocyte antigen-antigen d related, CD5, CD11c, CD20, CD22, CD38, limited FCM-7 antigen, no κ-or λ-polyclone, and accounted for 0.5% of nuclear cells.…”
Section: Case Reportmentioning
confidence: 99%